PENGARUH LINGKUNGAN KERJA, KEPUASAN KOMPENSASI, DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA PEGAWAI PADA PDAM TIRTA MOEDAL KOTA SEMARANG - Oktaria, Rifka Anissa; Nugraheni, Rini (Diponegoro Journal of Management, 2017)
This research was motivated by the   problems that often occur about the work discipline of the employee in PDAM Tirta Moedal Semarang City. Various violations that often occur indicate that the lack of understanding and understanding about what is the discipline of their own work both in written and non-regulatory rules that exist in the company. The purpose of this study to analyze the influence of work environment, compensation and work motivation to work discipline PDAM Tirta Moedal employees Semarang City.This research used independent variables such as work environment, satifaction compensation, and work motivation, as well as the dependent variable is the work discipline. Populations used were all employees of PDAM Tirta Moedal Semarang City. The sampling technique used methode used Proportionate Stratified Random Sampling and obtained the sample of 71 people. Data  analysis  methods  used  are  quantitative  analysis  including  variable  index,  validity  and reliability, the classic assumption test, multiple linear regression analysis, t test, F test, and the coefficient of determination (R2).Based on multiple linear regression test, the results indicate that the work environment have a positive relationship and a significant influence on the work discipline. Satifaction compensation have a positive relationship and a significant influence on the work discipline. And the last one, work motivation have a positive relationship and a significant influence on the work discipline. The coefficient of determination shows that the work discipline are influenced by work environment,  satifaction  compensation,  and  work  motivation  by  49,2% ,  while  the  remaining 50,8%are influenced by other variables in which the research did not examined in this study.